Nursing Students' Perception of Instructor Caring Behaviors in Zanjan Province in 2021 - Azar Eshghi; Nasrin Bahrami Nejad; Nasrin Jafari Varjoshani (Zanjan University of Medical Sciences and Health Services, 2022)
Background: Instructors' caring behaviors are regarded as one of the most impressive factors in the process of clinical training which is significant to promote the students' self-efficacy and self-confidence. Thus, it is of great importance to identify and promote the instructors' caring behaviors. Objectives: This study was performed aiming to determine the students' perception of instructors' caring behaviors in Zanjan province. Methods: This is a descriptive cross-sectional study which was conducted in 2021 on 235 nursing students of bachelor degree from the 4th semesters onwards in Zanjan province who were included in the study by stratified random sampling. To collect data, the questionnaires of demographic information and "Nursing Students Perception of Instructor Caring" were used. Statistical analysis was performed by independent t-test, and one-way analysis of variance (ANOVA) using SPSS software version 25. Results: The meanSd of instructors' caring behaviors was 126.37±14.70. The highest and lowest mean scores were related to the dimensions of respectful sharing (5.08) and control versus flexibility (3.26) respectively. There was a statistically significant relationship between creating a supportive learning climate and students' marital status (t=-1/9, p=0.05) and also between the appreciation of life's meaning and control versus flexibility with students' semesters (p<0.05). Conclusion: From the perspective of nursing students, the instructor's caring behavior was in average level. Therefore, it is recommended to take action in order to improve the instructors' caring behavior through training workshops.